Implementasi Genially Sebagai Media Pembelajaran untuk Meningkatkan Hasil Belajar Siswa dalam Mata Pelajaran Informatika Kelas VII di SMPN 2 Darma - Prayoga, Ikhsan; Gustiana, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Due to the traditional methods, the information teaching in this school is rather boring. The purpose of this study is to increase student learning outcomes using genially media materials. Seventy seventh-grade students participated in a quantitative quasi-experiment at SMP Negeri 2 Darma. The genially result is really effective. The siswa rata-rata nilai increased dramatically after using this media, going from 49,71 to 75,71. Uji-t indicates a significant increase (8,041 > 1,690), hence the hypothesis is accepted. Overall, student response was also quite positive (rata-rata 69,60), which is higher than previous methods. Overall, it has been successful in significantly increasing student learning outcomes and motivation in information.